Cellular MR Imaging - Michel Modo; Mathias Hoehn; Jeff W.M. Bulte (Molecular Imaging)
Cellular MR imaging is a young field that aims to visualize targeted cells in living organisms. In order to provide a different signal intensity of the targeted cell, they are either labeled with MR contrast agents in vivo or prelabeled in vitro. Either (ultrasmall) superparamagnetic iron oxide [(U)SPIO] particles or (polymeric) paramagnetic chelates can be used for this purpose. For in vivo cellular labeling, Gd 3+ - and Mn 2+ - chelates have mainly been used for targeted hepatobiliary imaging, and (U)SPIO-based cellular imaging has been focused on imaging of macrophage activity. Several of these magneto-pharmaceuticals have been FDA-approved or are in late-phase clinical trials. As for prelabeling of cells in vitro, a challenge has been to induce a sufficient uptake of contrast agents into nonphagocytic cells, without affecting normal cellular function. It appears that this issue has now largely been resolved, leading to an active research on monitoring the cellular biodistribution in vivo following transplantation or transfusion of these cells, including cell migration and trafficking. New applications of cellular MR imaging will be directed, for instance, towards our understanding of hematopoietic (immune) cell trafficking and of novel guided (stem) cell-based therapies aimed to be translated to the clinic in the future.